Selected Scientific Works of Hans Christian Orsted. - Ørsted, Hans Christian (Princeton legacy library., 2014)
Hans Christian Ørsted (1777-1851) was one of the leading scientists of the nineteenth century, having played a crucial role in founding electromagnetism. Unfortunately for the English-speaking world, almost all of his research was published in other languages, particularly his native Danish. This book will help to elevate Ørsted to his rightful place in the history of science by finally making his most important scientific works available in English. The book includes, for example, Ørsted's account of his revolutionary experiments in electromagnetism. In 1820, he discovered that a com.